SISTEM PENGONTROLAN TANGKI AIR MENGGUNAKAN SENSOR MAGNETIK VIA GELOMBANG RADIO - Emia Indahsari Ginting; Kurnia Brahmana (Saintia Fisika, 2013)
Abstract : A water tank control has been designed using wireless radio communication. The main control is taken by ATMega8 with its internal ADC where the sensors were placed. The level of the water in the tank is transmitted with two ways communication using standard UART data format. The system is worked as it is proposed.